2014
DOI: 10.1038/ejcn.2014.35
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-rich foods, cardiovascular diseases and all-cause mortality: the Rotterdam study

Abstract: Elderly with a higher NRF9.3 index score, indicating more beneficial components and/or less limiting components, had a lower risk of all-cause mortality. Consuming a nutrient-dense diet may improve survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 37 publications
2
40
0
2
Order By: Relevance
“…Several studies reported significant inverse associations of dietary scores with CVD and all-cause mortality in elderly men free from cardiovascular-metabolic diseases [4,5,7]. Our results in healthy men are in line with those of Hamer et al on a Mediterranean-style dietary pattern [10] and Streppel et al on the NRF9.3 score who observed no association with all-cause mortality in healthy men [24]. One explanation for the different associations in men with and without cardiovascular-metabolic diseases could be that only 17% of the healthy men were on a prescribed diet compared to more than 54% of the diseased men.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies reported significant inverse associations of dietary scores with CVD and all-cause mortality in elderly men free from cardiovascular-metabolic diseases [4,5,7]. Our results in healthy men are in line with those of Hamer et al on a Mediterranean-style dietary pattern [10] and Streppel et al on the NRF9.3 score who observed no association with all-cause mortality in healthy men [24]. One explanation for the different associations in men with and without cardiovascular-metabolic diseases could be that only 17% of the healthy men were on a prescribed diet compared to more than 54% of the diseased men.…”
Section: Discussionsupporting
confidence: 92%
“…This approach allowed us to examine the effects of specific nutrients on consumer attention within individuals, unlike FOP manipulations that present nutrients unsystematically [ 18 , 19 ] and to relate specific nutrients to healthfulness accuracy. As a manipulation check, we compared the nutrient density scores, which represent another approach to defining relative healthfulness (NRF9.3; [ 20 ]), of pairs of products and confirmed that the more healthful product in each pair had a higher nutrient density score, paired t-test, p < .001. Individuals were shown a pair of products on a single screen and were asked to identify the more healthful choice by clicking on a button below the product of their choice.…”
Section: Methodsmentioning
confidence: 87%
“…When looking at the contribution of food groups to the individual NRF9.3 index scores in the study population, it was seen that vegetables, cereals and dairy products had the largest contribution. Within the Rotterdam Study, we have previously found that the NR9, LIM3 and NRF9.3 index scores were associated with all-cause mortality, but not with major CVD events ( 4 ) . We have discussed that this might have been caused by the fact that individual weighted NRF scores not only depend on the NRF score on the food-item level, but also on which products are eaten and in which amount.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously evaluated the NRF index in terms of association with all-cause mortality and CVD among 4969 individuals aged 55 years and older from the Rotterdam Study. The NRF9.3 index showed to be inversely related to overall mortality, but not significantly with incident CVD ( 4 ) . To test the performance of nutrient profile models such as the NRF index, they should also be compared with each other and with other measures of a healthy diet.…”
mentioning
confidence: 99%